Bioethanol dehydrogenation over copper supported on functionalized graphene materials and a high surface area graphite. (June 2016) - Morales, M.V.; Asedegbega-Nieto, E.; Bachiller-Baeza, B.; Guerrero-Ruiz, A.
Abstract: A high surface area graphite and three functionalized graphene materials (one undoped and two N-doped prepared by different methods) synthesized by thermal treatment of a graphitic oxide were used to support copper catalysts, which were comparatively evaluated in the bioethanol dehydrogenation reaction. The characterization of the carbon supports by nitrogen physisorption isotherms, X-ray diffraction (XRD) and X-ray photoelectron spectroscopy (XPS) allowed us to stablish differences in the structure and chemical nature of the surface properties generated by the different synthesis procedures. Furthermore, reduced copper catalysts were characterized by XRD, transmission electron microscopy to determine the Cu nanoparticle sizes and their morphologies and XPS to obtain information on the Cu surface species. It was found that catalytic properties depended on the nature of each support, because it induced significant differences on metal nanoparticles, i.e. modifications of structural properties, as consequence of specific metal-graphite or metal-graphene interactions. Comparative studies with copper supported on a commercial silica gel highlighted the application of these carbon supported Cu catalysts as a promising alternative in terms of activity, selectivity and stability for the dehydrogenation of bioethanol into acetaldehyde. Also these Cu/graphite or Cu/graphene materials displayed high stability even when water is co-fed with ethanol.